Scale of hospitality firms and local economic development - Evidence from Crete - Andriotis, Konstantinos (My University, 2002)
The hospitality industry generates benefits for many host communities including employment generation and foreign exchange earnings. However, the hospitality industry often leads to external dependency contributing to a loss of local control over resources, migrant workforce and leakages outside the local economy, seriously reducing industry's potential for generating net financial advantages and growth for the local economy. Despite the variation of size of hospitality firms, there is still limited research on how well different size hospitality firms contribute to local economic development, something which this paper addresses, taking as a case the island of Crete. The findings suggest that the smaller the size of hospitality firm the larger the benefits to the local economy.
Keywords: Crete; Economic development; Hospitality firms; Scale